Pengaruh Kualitas Produk, Promosi terhadap Brand Image dan Keputusan Pembelian - Fahlia, Alya; Tuti, Meylani (Indonesian Journal Publisher, 2025)
This study aims to examine the influence of product quality and promotion on brand image and consumer purchasing decisions. The research was conducted on consumers of Wingstop at Mall Kasablanka Jakarta from January to March 2025. A total of 202 respondents were selected using incidental sampling. The data were analyzed using Structural Equation Modeling (SEM) with the assistance of SmartPLS software. The findings reveal that product quality has a significant effect on both brand image and purchasing decisions. Promotion significantly influences brand image but does not have a direct effect on purchasing decisions. Furthermore, brand image is found to significantly influence consumer purchasing decisions. These results highlight the critical role of brand image as a mediating factor in shaping consumer behavior. Therefore, it is essential for companies to maintain and enhance product quality, as it directly contributes to a strong brand image and encourages purchase decisions. In addition, promotional strategies should be reassessed and refined to more effectively shape positive consumer perceptions, which in turn can strengthen brand image and indirectly influence purchasing behavior. These insights are vital for businesses in developing integrated and impactful marketing strategies to improve competitiveness in the marketplace.